Proceedings of the 1st International Conference on Advanced Multidisciplinary Research (ICAMR 2018) 2019
DOI: 10.2991/icamr-18.2019.136
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Fats Percentage on Cardiovascular Resistance for Futsal Athlete

Abstract: This study aims to determine the effect of body fat percentage on cardiovascular endurance for futsal athletes. This study is an experimental design. The population in this study were Futsal athletes of Faculty of Sports Science, Universitas Negeri Makassar. There were ten Futsal athletes selected by purposive sampling technique. The data analysis technique used is descriptive statistics. Examining the reliability of the data, the researchers did a normality test before calculating the t-test. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…The results of this study are in line with research conducted by Anjali et al [5] concerning the relationship between VO2max and body fat percentage in female athletes, which showed statistically higher VO2max values in female athletes who regularly exercised in their two-year career than in non-athletes. This study also demonstrated a negative correlation between VO2max and body fat percentage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are in line with research conducted by Anjali et al [5] concerning the relationship between VO2max and body fat percentage in female athletes, which showed statistically higher VO2max values in female athletes who regularly exercised in their two-year career than in non-athletes. This study also demonstrated a negative correlation between VO2max and body fat percentage.…”
Section: Discussionsupporting
confidence: 92%
“…Someone with the same height and weight will not have the same percentage of body fat, because the level of fat in the body is also affected by activities and daily diet. One study showed that athletes who tend to have a high percentage of body fat tend to have low VO2max values compared to athletes who have ideal or normal body fat percentages who will have good VO2max values [5]. So that the percentage of body fat sufficiently affects the amount of VO2max [6].…”
Section: Introductionmentioning
confidence: 99%
“…Permainan sepak bola bertujuan untuk mencetak gol sebanyak-banyaknya ke gawang lawan dan menjaga gawangnya sendiri agar tidak kemasukan gol dari lawan. Pertandingan sepak bola dimainkan oleh 2 tim dan masing-masing beranggotakan 11 pemain, lamanya durasi permainan sepak bola yaitu 90 menit dalam dua babak, setiap babak belangsung selama 45 menit (Saharullah, 2018). Teknik dasar permain sepak bola meliputi kemampuan menendang (passing), menendang ke gawang (shooting), menggiring bola (dribbling), menghentikan bola (control), menyundul bola (heading).…”
Section: Pendahuluanunclassified